Pengaruh Model Pembelajaran Take and Give terhadap Hasil Belajar Siswa pada Mata Pelajaran Bahasa Inggris Di SD IT Qurrota’ayun Belitang OKU Timur - Ana Theriana (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2019)
Research on "Is there any influence of the Take and Give learning model on student learning outcomes in English subjects in class VI SD IT Qurrota'ayun belitang OKUT"? and The purpose of this study is to: find out whether there is an effect of "Take and Give learning model on student learning outcomes in English learning of students grade VI SD IT Qurrota'ayun belitang OKUT?". The method used in this research is the experimental method. Data collection techniques are through documentation, test techniques, instrument testing techniques and data analysis techniques. Data were analyzed using Data Normality Test, Homogeneity Test, Hypothesis Test. Based on the results of the study it can be concluded that: (1) After analyzing the form of tests, it is known that the Take and Give learning model has a significant influence on the learning outcomes of English class VI SD IT Qurrota'ayun belitang OKUT. Based on the analysis of the data that has been done, the average student learning outcomes obtained in the experimental class are higher than students in the control class who are not treated. (2) Success in the learning process by applying the Take and Give learning model is very influential, because this learning model emphasizes the activeness of students to work together and speed and accuracy in learning activities so that learning outcomes increase.Keywords: Effect of Take and Give learning models, Student Learning Outcomes.